Temporary Employment Agencies in Ontario: Experiences of South Asian Immigrant Women - Aujla, Navneet (York University, 2016)
Informed by the feminist political economy perspective (FPE), this study examines the experiences of recent South Asian immigrant women working through temporary employment agencies in Ontario, paying particular attention to how social factors such as gender, race and immigrant status shape these experiences. As FPE pays attention to the interconnection between family, state and market, the study examines how women experience precariousness at work, within the household, and trying to settle and integrate. Based on analysis of twelve qualitative interviews and observations as a participant-researcher, findings indicate that recent South Asian immigrant women are funneled into agency work due to a variety of structural barriers, and that the lack of rights associated with agency work leaves them particularly vulnerable to exploitation and poverty. As such, it is proposed that changes must address a lack of security and enforcement of employment standards, and barriers to employment for women and recent immigrants.

La Babylone des marins : Marins hauturiers à Montréal 1851-1896 - Bélisle-Desmeules, David (Université de Montréal, 2016)
Le port de Montréal connaît un essor considérable dans la seconde moitié du 19e siècle. Des travaux de dragages en font une destination importante pour les navires transatlantiques qui visitent le port durant la saison de navigation. Ainsi, de mai à novembre, un grand nombre de marins qui œuvraient sur ces navires faisaient escale en ville. Cet essai s’intéressera à ces marins hauturiers de la marine marchande, qui représentent durant leur passage dans la métropole un groupe distinct tenu aux bords de la société coloniale montréalaise, durant leur passage dans la métropole. Les marins, physiquement présents au cœur même de la cité, sont pourtant considérés comme des êtres périphériques, attirant l’attention de la presse et de l’opinion surtout lorsqu’ils transgressaient les normes sociales. Nous décrirons une partie de leur activité à terre à partir de trois lieux du front portuaire que sont les bassins du port, témoins de noyades et de sauvetages, les quais adjacents, où le vol de marchandises est monnaie courante, et finalement la taverne du bord de l’eau, où les marins vont boire. Leurs comportements liminaux comme la consommation abusive d’alcool et la bagarre ainsi que leur proximité avec les classes laborieuses indigènes, font d’eux des suspects facilement amalgamés aux « classes dangereuses ». Les marins posent un défi à la bonne marche du commerce maritime. Ils forment un groupe hautement surveillé par les autorités. Une force spéciale, la Montreal Water Police, est d’ailleurs mise sur pied à cet effet le temps de la saison de navigation. En effet, les conflits que les matelots entretenaient avec leur capitaine, qui se soldaient parfois par des désertions ou des procès minaient la bonne marche des affaires. Cependant, les autorités tentèrent tout au long de la période de policer le marché de l’emploi maritime, volatil et violent, géré par un groupe d’embaucheurs (crimps), intermédiaires interlopes dont les marins sont à la fois les bénéficiaires et les victimes. Finalement, on avancera que, durant la seconde moitié du 19e siècle, la présence des marins a fait du front portuaire de Montréal un lieu qui s’apparente à un sailortown, espace à la fois physique et symbolique où s’exprime la culture maritime à terre.

Competition or Liberation? Implications of Labour Automation in the Context of Cognitive Capitalism - Burgess, Russell (Carleton University, 2016)
Technologies in the first half of 21st century are developing new abilities to perform autonomously and compete with humans directly in more and more tasks, opening up the future possibility of increasing labour substitution. Using the theory of Cognitive Capitalism to examine advanced economies as the most recent form of capitalism shows that in the modern economy work is increasingly central to the lives of individuals due to new cognitive labour which requires more worker engagement than industrial labour. This requirement has strengthened the direct coercive mechanisms of the increasingly precarious wage relationship and weakened alternate income sources. This dissertation argues that automation in this context could be harmful to individuals required to depend on work to survive and evaluates three policy options against the goal of freeing individuals from this institutional constraint to work so that they can continue to fully and freely participate in society if widespread automation occurs.

Invisible Worker(s), Invisible Hazards: An Examination of Psychological and Physical Safety Amongst Frontline Workers in Long-term Residential Care Facilities in the 'New' Global Economy - Campbell, Andrea Lynn (York University, 2016)
Research has consistently demonstrated that the long-term residential care (LTRC) frontline workforce encounters a range of serious health and safety hazards and risks that result in physical and psychological injury, illness, absenteeism, and related costs. Using the lens of feminist political economy, this dissertation explores the risks workers encounter on the frontlines of LTRC, how these workplace risks are shaped by broader social, economic, political, and historical factors, as well as the ways frontline workers resist, challenge, or shape the conditions of their work in this setting. My analysis of primary data is informed by interviews with 17 frontline workers working within for-profit, non-profit, and municipal LTRC facilities within Ontario and 2 key informants. Restructuring and reform of health and social care services under neoliberalism have profoundly transformed the character, funding, organization, and delivery of LTRC. These changes have serious implications for workforce configurations, the conditions of work and care, workplace health and safety, worker control over their labour, and capacities for worker resistance to the conditions of their work. Within the LTRC organizational hierarchy, frontline workers are of marginal status. The frontline workforce is composed predominately of women and increasingly marginalized immigrants and racialized groups, whose care labour on the frontlines is often naturalized, undervalued, and treated as unskilled and safe. This research provides evidence that restructuring and work reorganization processes, policies, and practices constitute a form of structural violence, which contribute to, intensify, and/or give rise to new sources of struggle, inequity, risk, violence, alienation, and exploitation on the everyday/everynight frontlines of LTRC.

Creative Management: Disciplining the Neoliberal Worker - Cruz, Trent (Western University, 2016)
This integrated article dissertation examines some of the new managerial practices that have emerged to handle cognitive capitalism’s ongoing need for creative, flexible labour power. The three articles included in this dissertation offer a glimpse into the widespread processes employed by management to regulate and discipline a workforce that must also be granted a degree of relative flexibility, creativity, and autonomy in order to be effective under post-Fordist conditions of production. The first chapter looks at the emergence of corporate improvisational training at the turn of the twenty-first century as an attempt to cultivate flexible and innovative workers, a move that ultimately succumbs to what Andre Spicer (2013) calls “organizational bullshit”—the deployment of cynical and self-serving discourse that functions to build confidence and legitimacy within workplaces where a clear sense of occupational purpose is lacking. Chapter two explores the recent trend of workplace mindfulness as a specific element of the now-prevalent 'wellness' discourses, which inevitably work to align workers' personal values with those of their employer. The final chapter involves an analysis of the working conditions of voice-over and motion capture actors in the video game industry and the processes of rationalization and neo-taylorization to which they are subjected.

Labour, Heritage, and the Politics of Difference: Working Class History Museums in the Changing City - DesRoches, Davina Marie (Queen's University, 2016)
As a contemporary communications medium, the museum has undergone significant reinvention and reorientation of purpose within the past several decades. While the late twentieth century saw the rise of a fundamental reimagining of the museum as a visitor-oriented space where questions of representation, ownership, and voice were of paramount concern, the early twenty-first century has seen a repositioning of museums as market actors with a role to play in the economic aspects of social life. This dissertation probes the growing disconnect between the rhetoric and practices enacted under the auspices of new museology and the ascendancy of corporatized values, interests, and operational forms in museum praxis. It is specifically concerned with working class history museums located in postindustrial urban environments, and seeks to explore and consider some of the inherent tensions in representing labour struggles and working class heritage in gentrifying, capitalist cities. The dissertation reveals that working class history museums face immense challenges in trying to reconcile being socially progressive and class-oriented while also maintaining relevance and success in gentrifying areas. It argues that these museums are embedded within political economic structures of power, and thus face considerable limitations in their efforts to act as meaningful sites of political or ideological contestation. Furthermore, by subscribing to the supposition that heritage resources can be used to spur gentrification and economic development, museums may unwittingly reinforce elite reimaginings of the urban environment. Three case studies are examined: the People’s Palace, a public museum in Glasgow, Scotland; New York City’s Lower East Side Tenement Museum; and finally, the Écomusée du Fier Monde, a small community museum located in the Centre-Sud neighbourhood of Montréal, Canada.

Mental Health in the Workplace: Unions' Role in Identifying and Combating Psychosocial Hazards - Edelson, Miriam Karin (University of Toronto, Ontario Institute for Studies in Education, 2016)
The world of paid work has shifted extraordinarily in the last several decades. Globalization, technology, lean production, the intensification of work, mergers and reorganizations and precarious work have all meant a toughening of the conditions for workers. Unions organize in these conditions, confronting issues of concern to workers. Very little has been written about the role unions play in trying to protect the psychological health of their members. The major question of this thesis is whether unions are identifying and combating psychosocial hazards in the workplace. The thesis adds to knowledge on this subject by analyzing two data sets. First I conduct an analysis of grey literature on the Internet about psychological health and safety concerns. Second, I explore a series of questions with union health and safety experts representing every major Canadian union from each sector of the economy. The questions probe how unions are dealing with psychosocial risks in the workplace, how unions are organizing resistance and building solidarity. My inquiry also explores the issue of how unions deal with return-to-work for workers who have been absent for mental health reasons. I am not a neutral observer: I write from the standpoint of workers. My work has a practical utility to the degree that it can be directly applied to these real life problems facing health and safety practitioners. It attempts to theorize that which these union specialists should do. It also tries to anticipate some practical problems they may need to solve in future as a result of current health and safety practices. I observe real life phenomena and develop theory around them. One of these is that unions resist employer restraints and power and in so doing bump up against managementsâ right to control production and dictate work organization. In this thesis, I show the fledgling ways in which unions are challenging managementsâ typical rights in the interests of better working conditions. I give evidence of three promising practices that unions are adopting and propose that these may be adapted further for initiatives in other sectors. I argue that workersâ psychological health is one potential winner of these strategies. I also propose that union representatives be educated to deal more empathically with members that are absent for reasons of psychological ill health, in advocating for them when they return and by building solidarity among co-workers.
Accepted: 2017-03-27T23:00:16Z

The Seeds of Divergence: The Economy of French North America, 1688 to 1760 - Geloso, Vincent (London School of Economics and Political Science, 2016)
Generally, Canada has been ignored in the literature on the colonial origins of divergence with most of the attention going to the United States. Late nineteenth century estimates of income per capita show that Canada was relatively poorer than the United States and that within Canada, the French and Catholic population of Quebec was considerably poorer. Was this gap long standing? Some evidence has been advanced for earlier periods, but it is quite limited and not well-suited for comparison with other societies. This thesis aims to contribute both to Canadian economic history and to comparative work on inequality across nations during the early modern period. With the use of novel prices and wages from Quebec—which was then the largest settlement in Canada and under French rule—a price index, a series of real wages and a measurement of Gross Domestic Product (GDP) are constructed. They are used to shed light both on the course of economic development until the French were defeated by the British in 1760 and on standards of living in that colony relative to the mother country, France, as well as the American colonies. The work is divided into three components. The first component relates to the construction of a price index. The absence of such an index has been a thorn in the side of Canadian historians as it has limited the ability of historians to obtain real values of wages, output and living standards. This index shows that prices did not follow any trend and remained at a stable level. However, there were episodes of wide swings—mostly due to wars and the monetary experiment of playing card money. The creation of this index lays the foundation of the next component. The second component constructs a standardized real wage series in the form of welfare ratios (a consumption basket divided by nominal wage rate multiplied by length of work year) to compare Canada with France, England and Colonial America. Two measures are derived. The first relies on a “bare bones” definition of consumption with a large share of land-intensive goods. This measure indicates that Canada was poorer than England and Colonial America and not appreciably richer than France. However, this measure overestimates the relative position of Canada to the Old World because of the strong presence of land-intensive goods. A second measure is created using a “respectable” definition of consumption in which the basket includes a larger share of manufactured goods and capital-intensive goods. This second basket better reflects differences in living standards since the abundance of land in Canada (and Colonial America) made it easy to achieve bare subsistence, but the scarcity of capital and skilled labor made the consumption of luxuries and manufactured goods (clothing, lighting, imported goods) highly expensive. With this measure, the advantage of New France over France evaporates and turns slightly negative. In comparison with Britain and Colonial America, the gap widens appreciably. This element is the most important for future research. By showing a reversal because of a shift to a different type of basket, it shows that Old World and New World comparisons are very sensitive to how we measure the cost of living. Furthermore, there are no sustained improvements in living standards over the period regardless of the measure used. Gaps in living standards observed later in the nineteenth century existed as far back as the seventeenth century. In a wider American perspective that includes the Spanish colonies, Canada fares better. The third component computes a new series for Gross Domestic Product (GDP). This is to avoid problems associated with using real wages in the form of welfare ratios which assume a constant labor supply. This assumption is hard to defend in the case of Colonial Canada as there were many signs of increasing industriousness during the eighteenth and nineteenth centuries. The GDP series suggest no long-run trend in living standards (from 1688 to circa 1765). The long peace era of 1713 to 1740 was marked by modest economic growth which offset a steady decline that had started in 1688, but by 1760 (as a result of constant warfare) living standards had sunk below their 1688 levels. These developments are accompanied by observations that suggest that other indicators of living standard declined. The flat-lining of incomes is accompanied by substantial increases in the amount of time worked, rising mortality and rising infant mortality. In addition, comparisons of incomes with the American colonies confirm the results obtained with wages— Canada was considerably poorer. At the end, a long conclusion is provides an exploratory discussion of why Canada would have diverged early on. In structural terms, it is argued that the French colony was plagued by the problem of a small population which prohibited the existence of scale effects. In combination with the fact that it was dispersed throughout the territory, the small population of New France limited the scope for specialization and economies of scale. However, this problem was in part created, and in part aggravated, by institutional factors like seigneurial tenure. The colonial origins of French America’s divergence from the rest of North America are thus partly institutional.

L’usage par les travailleurs étrangers temporaires des ressources proposées par le droit du travail : une contribution aux études portant sur l’effectivité du droit - Gesualdi-Fecteau, Dalia (Université de Montréal, 2016)
Au Canada, le nombre de travailleurs étrangers temporaires est en forte hausse et ce, depuis 2003. Les travailleurs étrangers temporaires ne disposent ni de la citoyenneté politique, ni de la résidence permanente; leur mobilité professionnelle est restreinte et leur durée de séjour est limitée et prédéterminée. Sur le plan formel, ces travailleurs bénéficient des protections prévues par le droit du travail nonobstant leur statut migratoire. Toutefois, plusieurs travaux ont démontré que les travailleurs étrangers temporaires occupant des emplois qui requièrent un niveau réduit de formation sont généralement moins enclins à dénoncer la violation de leurs droits au travail. Le droit du travail constitue-t-il un rempart utile pour ces travailleurs? À l’aide d’une méthodologie mixte impliquant notamment une enquête de terrain auprès des acteurs-clé, la présente thèse poursuit deux objectifs distincts. Sur le plan empirique, elle permet de mettre en lumière l’incidence du système d’emploi singulier dans lequel s’insèrent les travailleurs étrangers temporaires sur leur usage des ressources proposées par le droit du travail. Le recours à ces ressources n’est pas contingent et prédéterminé; il est inextricablement lié aux opportunités et aux contraintes avec lesquelles ces travailleurs composent. Cette recherche révèle également que les stratégies échafaudées par différents acteurs qui ne sont pas, sur le plan juridique, des parties au rapport salarial, ont une incidence significative sur l’usage du droit par ses destinataires ; leur impact dépend largement du pouvoir dont ces acteurs disposent dans le système d’emploi. Sur le plan théorique, cette thèse s’inscrit dans le champ plus large des études portant sur l’effectivité du droit; elle propose de distinguer entre l’étude des effets du droit et l’analyse de son usage. Elle présente, à cette fin, un cadre analytique permettant de saisir le rapport qu’entretiennent les destinataires avec le droit.
https://doi.org/1866/13502

Geopolitics, State-Formation and Economic Development in Quebec and Ontario - Gheller, Frantz (York University, 2016)
This dissertation challenges the prevailing periodization of Quebec and Ontario’s economic development in Canadian historiography by contrasting the specificity of capitalist social relations with the non-capitalist forms of social reproduction belonging to French Canadian peasants and Upper Canadian farmers in the colonial period. With a few notable exceptions, existing historical interpretations assume that capitalism was there, at least in embryo, from the colony’s very beginning in the guise of the fur trade, manufacturing, or a local bourgeoisie. By contrast, this thesis brings together, through a comparative perspective, different pieces of the interconnected histories of France, Britain, the United States, Ontario, and Quebec in order to show that capitalism did not arrive on the shores of the St. Lawrence River with the first settlers. The dissertation also brings together pieces of the uneven intra-regional histories of these regions, and provides a general reflection on how to systematically integrate the geopolitical dimension of social change into historical sociology, political economy, and comparative politics. As such, the question with which the thesis is concerned is not exclusively that of the transition to capitalism in Quebec or in Ontario, but more broadly the interrelated questions of state-formation and ‘late development’ in north-eastern North America. One of the main findings of the dissertation is that only with the development of industrial capitalism in the north-eastern United States were the conditions for the emergence of capital-intensive types of agriculture in rural areas of Quebec and Ontario put in place. American breakthroughs toward industrial capitalism irrevocably transformed the system-wide conditions under which subsequent agricultural evolution took place in neighbouring regions, generating a new geopolitical configuration in which customary peasant production continued to persist in Quebec alongside petty-commodity farmers in Upper Canada and the development of industrial capitalism in urban areas such as Montreal. These findings bring to the fore the need to directly address the ‘peasant question’ in order to understand the impact of the continued existence of a large peasantry on state-formation and the long-term economic development of Quebec during the period when industrial capitalism was emerging as a dominant feature of the North American economy.

Race, Labour, and the Postmodern Plantation: Jamaican Migrant Farmworkers in Canada's Seasonal Agricultural Worker Program - Hjalmarson, Kirsten Elise (University of British Columbia, 2016)
This ethnographic thesis project critically examines the experiences of Jamaican migrant farmworkers employed in the Okanagan Valley, British Columbia via the Seasonal Agricultural Worker Program (SAWP). First introduced in 1966, the SAWP is the oldest and longest-standing labour migration regime in Canada and the principal agricultural stream of the federal Temporary Foreign Worker Program. Drawing upon the salient work of numerous activists and scholars who have contended that the SAWP facilitates a form of transnational indentureship by bonding migrant workers to their employers, I argue that the SAWP farm site constitutes a peculiar and totalizing institution that capitalizes on the unfreedom of black labour. I apply critical race theory to situate workers’ experiences of surveillance, immobilization, and hyper-exploitation in addition to their characterization of farm life as “prison life” within a postslavery context. I conclude that only by acknowledging the role of racism and its relationship to the border can we ever hope to truly achieve justice for migrant farmworkers in Canada.

Athletic Labour, Spectatorship, and Social Reproduction in the World of Professional Hockey - Kalman-Lamb, Nathan (York University, 2016)
Existing literature in the sociology of sport largely omits any discussion of the relation between the spectator and athlete in professional and high performance sport. This dissertation explores that relation, demonstrating that exploitation in athletic labour and the enduring allure of sport as spectacle are inextricably linked as part of a broader political economy. The labour of professional athletes is theorized as a form of social reproductive labour that offers affective/subjective renewal for fans. Spectators who experience isolation and alienation in their day-to-day lives as capitalist subjects come to sport seeking a sense of meaning, connection, and community. Athletic labour in professional sport provides this to them and enables them to continue to function as productive capitalist subjects by serving as an armature upon which an imagined athletic community of fans can be built. However, for social reproduction to occur for fans, athletes must sacrifice their bodies completely in the performance of their labour. It is only through this sacrifice that the imagined athletic community becomes concretized as something tangible and real and spectators become willing to spend their money on sports fandom. This theoretical understanding of athletic labour and spectatorship is explored through semi-structured qualitative interviews with eight former professional hockey players and eight spectators of sport. The testimony of former players consistently links the political economy of professional sport and the harm and exploitation they experienced in the course of their work. The testimony of spectators, on the other hand, typically fails to acknowledge that the meaning and pleasure derived from watching professional sport is predicated on the destruction of athletic bodies. This study ultimately suggests that a form of alienation exists between athletes and spectators. The spectator grasps for an elusive sense of community within a society structured to deny that form of connection by placing vicarious investment in the bodies of athletes. Yet, this act of investment instrumentalizes and commodifies the athlete. Athletes understand this process as it occurs because it denies them their humanity by transforming them into something both more (the heroic vessel) and less (the abject failure) than human.
Keywords: Exploitation; Hockey; Imagined community; Injury; Interviews; Labor; Labour; Labour relations; Marxism; Masculinity; Political economy; Qualitative methodology; Social reproduction; Social theory; Spectatorship; Sport

Principles and Processes for Food Sovereignty: An Evaluation of the Blueberry Sector in British Columbia - Klassen, Susanna (Susanna Elsie) (University of British Columbia, 2016)
As a concept that has increasingly been invoked in discussions of social and political food systems dynamics, food sovereignty calls for the holistic consideration of human and ecological aspects of agricultural systems with a focus on power and political dynamics. We investigated an export-oriented agricultural production system as a case study to understand how and to what extent food sovereignty principles can be enacted in the context of agriculture in the Global North. The blueberry industry in British Columbia, Canada, is socially and economically significant within a regional food system, and is globally integrated through export and trade. This study employs the framework of food sovereignty by drawing on principles of equity, empowerment and ecology as a methodological tool for assessing food systems, and examines how local producers in the BC blueberry industry are responding to pressures, constraints and opportunities in the global food system. I identified and operationalized key principles and processes for food sovereignty in the form of indicators. I conducted 33 structured interviews with blueberry growers representing a range of scales and modes of production. Significant themes and dynamics related to food sovereignty discussed by growers were: high demands for seasonal labour leading to mechanization; blueberry production as a means to attain a farming lifestyle while supplementing with significant off-farm income; and a perceived lack of power among growers relative to other actors in the food system. Participants expressed reduced decision autonomy through resource constraints and economic pressures. The combination of economic forces and social dynamics that have most growers locked into an industrial production cycle represent a barrier to achieving food sovereignty principles. On the other hand, there were several important institutions in the industry that support and empower growers through democratic participation opportunities, knowledge translation, and field expertise. A significant re-orientation of food systems governance and policy combined with economic re-structuring and social empowerment mechanisms would be needed to approach the realization of food sovereignty principles in the BC food system.

Deindustrialization on the Periphery: An Oral History of Sydney Steel, 1945-2001 - MacKinnon, Lachlan (Concordia University, 2016)
This thesis is an historical examination of the multi-layered processes of deindustrialization in Sydney, Nova Scotia. The history of a steel plant formerly located in the centre of the city is used as a case study through which the mechanisms of deindustrialization are fully explored. In 1967, the provincial government of Nova Scotia nationalized the Sydney Works. This marks a significant divergence from previous studies of deindustrialization, which have traditionally focused on the wave of industrial closures in the North American heartland during the 1970s and 1980s. Framed by oral history accounts of former steelworkers, this dissertation reveals the combined impact of Canadian regionalism, political economy, and working-class cultures of resistance on local experiences of industrial decline. This represents a synthesis between the econo-political historiography of deindustrialization favoured in the 1980s and the cultural/representational approaches of the 1990s and 2000s. The title, “Deindustrialization on the Periphery,” speaks to the specific national and regional contexts that frame the decline of Sydney Steel. The longue durée of economic change on the rural resource frontier has been understudied. In Cape Breton, the devastation wrought by the end of industry has roots that stretch back to the early 20th century. Tracing these through the use of Harold Innis’ “staples trap,” my thesis reveals how deindustrialization stretches from decades before closure to the years after a mine, mill, or factory are shuttered for the last time. Workers and other residents in Sydney continue to face the bodily aftermath of workplace injury, occupational, and environmental illness long after the structures of the plant have been demolished. But so, too, have experiences of working at the mill and living in the neighbourhoods that surrounded its gates created particular forms of culture, solidarity, and identity. My research is more than a eulogy for a defunct steel town. It seeks to expose the tensions between different forms of memory and experience, and to examine how the industrial past remains inextricably connected to the “post-industrial” present.
https://cha-shc.ca/prize-winner/lachlan-mackinnon/

Up-Rooted Lives, Deep-Rooted Memories: Stress and Resilience Among Jamaican Agricultural Workers in Southern Ontario - Mayell, Stephanie (McMaster University, 2016)
The Seasonal Agricultural Worker Program (SAWP) is a transnational labour agreement between Canada, Mexico, and various Caribbean countries that brings thousands of Jamaican migrant workers to Canada each year to work on farms. This thesis explores Jamaican SAWP workers’ experiences of stress in Ontario, and situates these experiences within a system of power and international inequality. When describing their experiences of stress and suffering in Ontario, many Jamaican workers drew analogies between historic and modern slavery under the SAWP. However, stress discourses also inspired workers to emphasise their resilience, and many workers gave equal attention to explaining their inherent strength as “Jamaicans”, which they associate with national independence and the history of slavery. In this way, I suggest stress discourses are sites of flexibility and resilience for Jamaican workers, and this thesis presents the foremost cultural, political, and historical factors that support Jamaican workers’ resilience in Ontario. Moreover, the predominant coping strategies workers employ in Ontario will be explored within the context of their restricted agency under the SAWP. This thesis concludes with a discussion of stress as an expression of subjectivity that is characterised by strength, faith, and the history of slavery.

Dressing Down Migrant Sex Work: The Global Anti-Trafficking Regime, Legal Employment Rights, and Canada’s Temporary Foreign Worker Program - Montiel, Vasti (Toronto Metropolitan University, 2016)
This paper analyzes the contemporary global anti-trafficking regime and discusses the destructive influence this regime has had on the lives of migrant sex workers. Through the use of public documents and academic literature, I deconstruct the global anti-trafficking discourses and argue in favour of more viable rights-based solutions (e.g., labour rights, immigration rights, and sexual rights) for combating human trafficking. Within this analysis, I explore the Canadian government’s gradual commitment to combat human trafficking through the gradual discontinuation of the exotic dancer visa, and eventual implementation of the migrant sex worker ban. In formalizing its commitment to combating trafficking, the Canadian government has implemented restrictive policy measures terminating migrant women’s ability to legally access the Canadian sex industry. While this type of employment was problematic in many ways, the Canadian government should have addressed these issues through rights-based policy initiatives instead of prohibiting access as part of its anti-trafficking campaign

Towards Transformative Solidarities: Wars of Position in the Making of Labour Internationalism in Canada - Nastovski, Katherine Slavka (York University, 2016)
Within the broad debates about neoliberalism, neoliberal globalization and the declining power of unions in the Global North, there has been renewed interest in the possibilities of international and transnational labour solidarity, coordination and action. Drawing from Rebecca Johns (1998) distinction between transformative and accommodationist forms of international labour solidarity I argue that we need to critically assess how these practices challenge or reinforce global divisions of labour born of the historical development of capitalism. To this end, this study provides an analysis of the dialectical relationship between the dominant practices of labour internationalism that emerged within the organized labour movement in Canada during the Cold War. I examine both the challenges to and possibilities for building transformative forms of international labour solidarity today. Challenges include the philosophies of social partnership, racism, white supremacy and nationalism that informed the labour imperialism and accommodationist solidarities of the institutionalized internationalism in this period. I argue that the brand of social democratic anti-communism that characterized this institutionalized labour internationalism was shaped by the wars of position over worker justice happening on the national level and internationally between unions, but also by ideas of race and nation. I outline the lessons from these practices by focusing on four cases: Kenya, Southeast Asia, The Caribbean and Palestine. Finally, I assess the grassroots labour solidarity that re-emerged inside the labour movement with the rise of the New Left. I argue that the model of international solidarity they built, called worker-to-worker, arose from the goals and strategies of class struggle unionism and constitutes an example of transformative solidarity that can inform discussions about organizing international soldiarity today. Rooted in anti-racist Marxist feminist theory, my historical sociological analysis draws from both archival research and interviews with union leaders, activists and staff. I make sense of the solidarities that determined these practices by exploring the terrain of class consciousness in which they were formed. Situating my analysis within the social and political contours of class formation in Canada and internationally, I pay particular attention to how these practices of labour internationalism intersect with issues of race, gender, nation and class struggle, and how racialized and gendered class formation in Canada has influenced ideas of worker justice and responses to imperialism, colonialism and national borders.

Les nouvelles formes de servitude et le rôle du droit : le cas de la privation de mobilité des travailleurs agricoles migrants au Canada - Ollivier-Gobeil, Jeanne (Université du Québec à Montréal, 2016)
Depuis le milieu des années 1960, le gouvernement canadien organise la migration temporaire de travailleurs agricoles originaires principalement des Caraïbes et d'Amérique centrale, via deux principaux programmes, soit le Programme des travailleurs agricoles saisonniers (PTAS) et le Volet agricole du Programme des travailleurs étrangers temporaires. Ces programmes ont permis de faire venir au Canada près de 42 530 travailleurs agricoles temporaires en 2013, dont 9760 au Québec seulement. Le PTAS et le Volet agricole soulèvent toutefois les critiques de plusieurs organisations et chercheurs. Une caractéristique commune centrale de ces programmes est particulièrement décriée, à savoir l'assignation des travailleurs à un employeur unique et à un emploi spécifique, puisque celle-ci aurait pour effet de priver les travailleurs de leur mobilité sur le marché du travail. En ce sens, il est notamment reproché à ces programmes de perpétuer des formes de travail non libre, alors que les travailleurs ne peuvent circuler librement sur le marché du travail. Dans la continuité de ces travaux critiques, ce projet de recherche se propose d'examiner le rôle de cette disposition juridique comme mécanisme de privation de la mobilité des travailleurs. Plus précisément, l'objectif de ce mémoire est d'analyser le rôle double du droit, d'une part, dans la production et l'encadrement de ces formes de travail non libre, et d'autre part, dans la possible contestation de celles-ci. Pour ce faire, nous nous appuierons tant sur analyse à la fois théorique et historique, que sur une vaste enquête de terrain. Cette enquête s'inscrit dans un projet de recherche plus large - dirigé par le professeur Martin Gallié - ayant permis de réaliser près de cent entretiens avec des travailleurs du PTAS et du Volet agricole de la région de Saint-Rémi, au Québec.

Job Displacement and the Implications for Job Quality: An Investigation of the Job Transition Process for Public Sector Workers in Scotland, Uk and Ontario, Canada During the Great Recession - Pascoe-Deslauriers, Rachelle M. (University of Strathclyde, 2016)
This thesis conceptualises the job transition as a continuous process in the context of organisational downsizing and restructuring. It argues that the policy and research related to re-employment following job loss, organisational downsizing and relevant labour market interventions remains disconnected from, and hence underemphasises, the sequential and cumulative nature of the transition process while also focussing disproportionately on modifying individual behaviour and action. This study explores the intersection and overlap in factors, actions and decisions made by actors in each part of the transition process to better understand the dynamic nature of job transition and its implications for re-employment and future job quality. This research considers job transition from two forms of displacement – job displacement and worker displacement. It comprises a cross-national comparative study of displacement from public sector work in Ontario, Canada and Scotland, UK. Forty expert and stakeholder interviews were carried out addressing different aspects of job transition, targeting academic and policy experts, employers/senior managers, union representatives and labour market programme service providers. Furthermore, 38 semi-structured work history interviews were conducted with displaced workers along with a follow-up survey. This research argues that downsizing policy and labour market interventions appear to view any job as a better outcome than redundancy. Where organisational policies maintain employment, the emphasis is on maintaining extrinsic features of work. Through practices like salary protection and lateral transfers, good quality work beyond equivalent remuneration is a bi-product rather that a central consideration. The study finds that individuals, faced with particular processes and limited information, modify their behaviour to protect valued aspects of work including, but not limited to, extrinsic job factors. Conceptually, this research contributes to knowledge on job loss and re-employment, organisational downsizing practice and job quality. Empirically, it contributes to debates on public sector restructuring following the Great Recession of 2008.

Insights into Nurses’ Work: Exploring Relationships among Work Attitudes Work-related Behaviours - Perreira, Tyrone (University of Toronto, Institute of Health Policy, Management and Evaluation, 2016)
Work motivation has been associated with work productivity. In health care, low motivation levels are associated with low productivity and linked to poor performance, decreased patient safety, and overall poor quality care. Hence the importance, ascribed in the literature, to clearly identifying the relationships between and among factors associated with work motivation, including work attitudes, and behaviours linked to work performance such as extra-role behaviours. Despite their importance to performance in health care, these relationships are understudied and poorly understood. The purpose of this study is to better understand work attitudes and their relationships to one another and to extra-role behaviours amongst nurses working in hospitals, the community, and long-term care settings in Ontario. This study comprises two stages: first, a scoping review focused on identifying individual-, unit-level, and organization-level characteristics that influence work motivation in health service organizations. The findings from the scoping review, augmented by a more in-depth review of the literature, aided in the development of a conceptual framework that guided the second stage of the study, to examine relationships amongst a specific set of nurses’ work attitudes - including perceptions of organizational justice, perceived organizational support, and affective commitment - and extra-role behaviours – specifically, organizational citizenship behaviours - in Ontario health care settings. In the second stage of the study, a survey was developed and administered to frontline nurses actively working in hospitals, the community, and long-term care settings in Ontario. Relationships amongst the constructs of interest were examined using structural equation modeling and path analysis. Examining the relationships of these concepts in a single model is novel, and offers insights regarding their complexity. The analyses further suggest that prior studies may be under-nuanced, and approaches to conceptualizing the concepts of perceived organizational justice and affective commitment in particular may have led to erroneous conclusions regarding their associations with perceived organizational support and organizational citizenship behaviours. This study further addresses four significant gaps previously identified in the work motivation and work behaviour literature: (1) how affective commitment relates to behavioural efforts, specifically organizational citizenship behaviours; (2) utilization of reliable and validated instruments to study work motivation; (3) use of a sufficiently large sample to have empirical support for generalizability; and (4) examination of these phenomena, among nurses, across diverse health care settings.

Reaching Gold Mountain: Diasporic Labour Narratives in Chinese Canadian Literature and Film - Phung, Malissa (McMaster University, 2016)
This project provides a coalitional reading of Chinese Canadian literature, film, and history based on an allegorical framework of Asian-Indigenous relationalities. It tracks how Chinese labour stories set during the period of Chinese exclusion can not only leverage national belonging for Chinese settlers but also be reread for a different sense of belonging that remains attentive to other exclusions made natural by settler colonial discourses and institutional structures, that is, the disavowal of Indigenous presence and claims to sovereignty and autochthony. It contributes to important discussions about the experiences of racism and oppression that typically privilege the relations and tensions of diasporic and Indigenous communities but hardly with each other. What is more, this study aligns with a recent surge of interest in investigating Asian-Indigenous relations in Asian Canadian, Asian American, and Asian diaspora studies. The political investments driving this project show a deep commitment to anti-racist and decolonial advocacy. By examining how Chinese cultural workers in Canada have tried to do justice to the Head Tax generation’s experiences of racial exclusion and intersectional oppressions in fiction, non-fiction, graphic non-fiction, and documentaries, it asks whether there are ways to ethically assert an excluded and marginalized Chinese presence in the context of the settler colonial state. By doing justice to the exclusion of Chinese settlers in the national imaginary, do Chinese cultural workers as a result perform an injustice to the originary presence of Indigenous peoples? This thesis re-examines the anti-racist imperative that frames Chinese labour stories set during the period of Chinese exclusion in Canada: by exploring whether social justice projects by racially marginalized communities can simultaneously re-assert an excluded racialized presence and honour their treaty rights and responsibilities, it works to apprehend the colonial positionality of the Chinese diaspora within the Canadian settler state.

Temporary Foreign Workers in British Columbia: Unfree Labour and the Rise of Unscrupulous Recruitment Practices - Rodgers, Alexandra Ellen (Simon Fraser University, 2016)
The political and economic processes of neoliberalization have led to the intensification of worker exploitation. In Canada, Temporary Foreign Workers (TFWs) who enter through the Low-waged Streams of the Temporary Foreign Worker Program (TFWP) are amongst the most vulnerable to abuse and exploitation. This thesis uses theories on unfree labour, state transformation, and anti-racism, along with data generated through qualitative research, to examine the state legislated exploitation of TFWs in British Columbia. I argue that the unscrupulous recruitment of TFWs into British Columbia is the functional process through which labour flexibility and unfreedom is achieved within the larger project of neoliberalization. I conclude by considering how regulatory reform of labour markets can be used in conjunction with anti-racist and anti-imperialist political demands that aim to challenge the functional processes of neoliberalization.

A "Minor League Equivalent to the Eiffel Tower and the Empire State Building": Vancouver's Penthouse Nightclub - Shearman, Mary (Simon Fraser University, 2016)
The Penthouse is rumoured to be the oldest continuously operating nightclub in the land we now know as Canada and is without a doubt the oldest exotic nightclub. Owned and operated by an Italian family who emigrated to Vancouver, British Columbia, The Penthouse has survived numerous waves of moral crackdown in the city as well as many offers to buy the prime location in the face of aggressive development. A staggering number of nightclubs in Vancouver, exotic or otherwise, have not shared the same fate. Through conducting an institutional history of The Penthouse I locate it within changing local politics related to feminist activism, policing, and the sex industry as well as larger shifts in cultural attitudes towards sexual labour and sex workers' bodies. Further I assemble a social history of the dancers, looking at their experiences in the club and their perception of the intersections between feminism, identity, performance, and sex. Feminist theory, women's and gender history, and performance studies inform this multi-method project, which includes results and analysis from archival research and oral history interviews conducted with dancers employed at the club from 1978-2012. Overwhelmingly, the narrators reflected on their time as dancers as valuable to their lives in a myriad of ways, including helping to foster healthy relationships with their bodies and sexualities. Nevertheless most felt that the stigma they faced as sexual labourers impacted their lives in a negative way and was in conflict with the way they experienced their work themselves. This ongoing stigma was often a driving force for abandoning striptease for more 'square' or respectable work. Others continue to work in the sex industry. Eleven dancers shared their stories for this project, as did one member of the serving staff at The Penthouse, booking agent Randy Knowlan, and current owner/operator Danny Filippone. These stories offer a history of the Penthouse which places it as a central part of Vancouver's history. At a time when conventional striptease seems to be in decline and other facets of the sex industry seem to be under attack by new forms of criminal regulation, the interviews with dancers, staff, and the owner/operator suggest that future possibilities for Vancouver's contemporary striptease communities might lie in the evolving local neo-burlesque scene.
OCLC: 1125387295

Union Organizing in the Canadian Banking Industry, 1940-1980 - Smith, Julia Maureen (Trent University, 2016)
In this dissertation, I examine union organizing in the Canadian banking industry between 1940 and 1980. By demonstrating that bank workers consistently sought to unionize throughout the twentieth century, I challenge claims that bank employees and other private sector white-collar workers have low rates of unionization because they are not interested in unions or suffer from false consciousness. This research also suggests, however, that many bank workers saw themselves as different from blue-collar industrial workers; the lived reality of bank work as precarious, poorly paid, and rife with gender inequality intersected with ideas about professionalism and aspirations of advancing up the career ladder. Banks, unions, and workers drew on these ideas and experiences in their arguments for and against unionization. I also look at why previous organizing efforts did not establish a strong union presence in the banking industry. Most of these attempts failed, I argue, due to several key issues, including the banks’ anti-union activity, federal and provincial labour board decisions, and labour movement disputes over ideology, jurisdiction, and strategy. The banks consistently opposed unionization and used a variety of tactics to thwart union organizing, both overtly and covertly. The state, in the form of labour legislation and labour boards, provided unions and workers with some means by which to compel the banks to recognize unions, negotiate contracts, and deal with employee grievances; however, state action and inaction more often worked to undermine union organizing. The attitudes and strategies of high-ranking labour movement officials also shaped the outcome of union drives in the banks. Between 1940 and 1980, the mostly male labour leadership repeatedly used top-down organizing strategies and appointed male organizers with no experience of bank work to oversee union drives in a sector with an increasingly feminized workforce; labour leaders’ inability or unwillingness to reflect on this approach and to support grassroots campaigns and alternative strategies hindered bank union organizing. I thus highlight the intersection of gender and class and reveal how these factors have historically shaped the labour movement bureaucracy, union organizing, and the relationship between labour and the state. Author Keywords: banks, gender, labour bureaucracy, trade unions, union organizing, white-collar workers.
https://cha-shc.ca/prize-winner/julia-smith/

Precarious Work in Montreal: Women, Urban Space, and Time - Teeple Hopkins, Carmen (University of Toronto, 2016)
This dissertation examines the impact of precarious work on women in Montreal. Precariousness is increasingly common in Quebec, where women are overrepresented in part-time, temporary, and self-employed work. Based on three years of fieldwork, the thesis argues that while many women experience precariousness in the labour market, they do not experience it in the same ways. The neighbourhoods in which women live significantly shape their lives at work and home. Building critically on the literature on precariousness and social class, my research theorizes precarious workers as members of the working class, not as a marginalized social class outside it. Specifically, the dissertation asks how urban space influences precarious work and how time pressures impact experiences of work and home. First, while noting that precarious workers across industries (e.g. art, teaching, service) face housing pressures similar to those experienced by other members of the working class, the research shows that precarious women workers living in central neighbourhoods are especially at risk of being displaced by the middle-class. Second, the project brings important attention to paid and unpaid domestic work. Most research in the field of “time-use” at work focuses on sectors outside the home, even though women have long performed unwaged housework and many women continue to undertake paid employment or self-employment in the home. The dissertation demonstrates the ways in which women’s workloads have increased in the sphere of the home, diminishing their physical health and rendering them more precarious. Third, with reference to women who continue to perform large amounts of unpaid work, the research considers the relevance of historical and contemporary debates around the relationship between paid and unpaid labour, illustrating how women’s wages are negatively impacted by this unpaid work. This dissertation brings together the social dimensions of gender, race, social class, and urban space. In so doing, the project contributes a multi-scalar analysis to antiracist feminist political economy and reaffirms the importance of social class within feminist geography. Bridging these two broader traditions – political economy and economic geography – the project provides a critical framework for understanding the specificities of precarious work for women in Montreal.

"Comrades! I Am Far from You, but I Am with You!": Ukrainian Working Women, Transnationalism, and the Soviet Cultural Revolution in Winnipeg, 1928 - Vargscarr, Karolya (University of Manitoba, 2016)
Using local primary sources, this work answers two questions. Firstly, is there a transnational political connection, reflected ideologically or materially, between the readership of Robitnytsia in Winnipeg and the Soviet Union in 1928? Secondly, what are the interests of the readership of Robitnytsia, as reflected in the Letters section? The answers to these questions are relevant to social historians because their focus is on content generated by the female readership of the journal, not the content generated by the male activists and political leaders who both contributed to and edited it. This work also highlights the value of Robitnytsia as a historical source of Canada, labour, gender, women's, and transnational histories; one that has been under-utilized to date and is readily available to researchers in Winnipeg and other cities across Canada. To evaluate and provide an analysis of Robitnytsia as a source of primary evidence, a brief introduction to the ULFTA, Robitnytsia, and the Soviet Cultural Revolution is helpful to the reader. After addressing the relevant historiography, the three chapters that follow provide analysis and the relevant context for the source work, including photographs and illustrations from the journal. Photographs featured on the covers of Robitnytsia provide insight into the imagery of the journal, as well as to the rhetoric associated with well-known images and icons within the working class Ukrainian community in Winnipeg. Discovering the answer to the second question posed in this work was straightforward, as the priorities and interests of the working women in Winnipeg were highly localized and specific, including recognizable and accessible priorities to even those readers who are not familiar with the work of the ULFTA. These interests included basic literacy, education, labour organization, and participation in political and social activities. The evidence regarding a transnational link to the Soviet Union, the first question of this work, was even more clear: at the grassroots level, there was no such transnational link between the Ukrainian Left in Winnipeg and the Soviet Union in 1928. –From Introduction

Accumulating Cares: Women, Whiteness, and the Affective Labour of Responsible Reproduction in Neoliberal Times - Watson, Amanda (University of Ottawa, 2016)
This thesis examines contemporary popular and news media representation of motherhood and labour in Canada and the United States. I explore what texts about motherhood and maternal labour suggest about gendered responsibilities to citizenship in neoliberal conditions. Building on important feminist research in the fields of citizenship, care, and the welfare state, I ask how are mothers being socially responsibilized toward multiple forms of labour simultaneously and to what effect? By engaging feminist theories of citizenship and bridging this field with feminist theories of science, media, and affect, I demonstrate how, under neoliberal conditions and in precarious circumstances, the ways in which women appear to juggle their commitments to paid and unpaid labour, determines how mainstream discourses reflect their value as citizens. This dissertation uses feminist critical discourse analysis to assess how, as women are responsibilized toward unpaid intimate work in newly empirical ways at the same time that they are encouraged to pursue career success in full-time paid employment, contemporary women in Canada and the United States are encouraged to rise above welfare retrenchment and inadequate provision by juggling “it all.” My thesis is an intersectional feminist project that interrogates questions of gendered citizenship and maternal affect, and I join feminist political theorists in applying pressure to the field of citizenship studies to centre reproduction in discussion of gendered welfare.

Green Jobs: An Alternative to Neoliberalism? Recycling in Buenos Aires, Argentina and Toronto, Canada - Yap, Lilian (York University, 2016)
In recent years, environmental organizations and labour unions have begun to more seriously campaign for the promotion of green jobs as a way to address the twin problems of climate change and economic stagnation, particularly in the aftermath of the financial crisis of 2008. They variously suggest that green jobs will be created through increased investment in green sectors; for some, this requires public investment and the adoption of a Green New Deal (GND) policy orientation, while for others this requires only increased private investment in green industries. The former emphasize that since green sectors are more labour-intensive than traditional industries, investment in green infrastructure could thus generate comparatively more employment per dollar invested. At the heart of these proposals is the proposition that capitalist economic growth could be made consistent with social and ecological justice. This dissertation is a critical engagement with the propositions of the green jobs campaign through the concrete examination of two diverse cases of residential (i.e. post-consumer) recycling, a quintessentially green sector, in Buenos Aires and Toronto. Defining recycling as the (global) production of value from waste, the analysis pays particular attention to both the labour process and historical development of recycling. Through a combination of qualitative document analysis, archival research, and qualitative interviews, this thesis argues that purely market-coordinated recycling is not able to simultaneously deliver large-scale employment creation and improved socio-ecological outcomes because of the inherent tension between labour intensiveness and methods of increasing productivity. This tension, in turn, is rooted in the distributive conflict characteristic of capitalist production, the resolution of which requires increased economic growth. From an ecological perspective, then, this is simply a deferment of the problem. In line with proponents of the Green New Deal, this dissertation argues that mediation of this tension in a direction favourable to both ecological and social concerns requires collective intervention. However, going beyond the Green New Deal, it concludes that commitment to social and ecological justice requires moving in the direction of decommodified, cooperative production and collective consumption.